2010
DOI: 10.1016/j.rmed.2010.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Utility of high-resolution computed tomography and BAL in cryptogenic organizing pneumonia

Abstract: The imaging findings and BAL could be useful for patients with appropriate clinical presentation and for those whose transbronchial biopsy is negative or for whom a confirmatory biopsy cannot be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…When the results were discordant, the investigators met as a group to reach consensus on the specific abnormality present. Radiographical features associated with each OP case were recorded, including location of the abnormality(s) (central, peripheral or diffuse), and the presence or absence of specific changes associated with OP as described in the medical literature, including any nodule/mass,11 consolidation,12 13 ground-glass component13 and air bronchograms 14. A pulmonary nodule or mass was defined as a radiographically distinct solid lesion surrounded on all sides by pulmonary parenchyma.…”
Section: Methodsmentioning
confidence: 99%
“…When the results were discordant, the investigators met as a group to reach consensus on the specific abnormality present. Radiographical features associated with each OP case were recorded, including location of the abnormality(s) (central, peripheral or diffuse), and the presence or absence of specific changes associated with OP as described in the medical literature, including any nodule/mass,11 consolidation,12 13 ground-glass component13 and air bronchograms 14. A pulmonary nodule or mass was defined as a radiographically distinct solid lesion surrounded on all sides by pulmonary parenchyma.…”
Section: Methodsmentioning
confidence: 99%
“…The BAL differential cell count typically demonstrates a mixed pattern, consisting in increased percentage of lymphocytes (20 to 40%), neutrophils ($10%), and possibly eosinophils ($5%). 4,45,48,[90][91][92][93][94] The percentage of lymphocytes is usually higher than that of eosinophils in patients with COP but may be higher in cases overlapping with CEP. 5,47,49,83,95 The presence of a small percentage of plasma cells or especially mast cells is remarkable.…”
Section: Biological Featuresmentioning
confidence: 99%
“…We congratulate Dr. Jara-Palomares et al 1 for their elegant and important study, which discusses the utility of highresolution computed tomography (HRCT) and bronchoalveolar lavage (BAL) in the diagnosis of cryptogenic organizing pneumonia (COP). They concluded that the association of the imaging findings and BAL could be useful for diagnosing COP in patients with appropriate clinical presentation, and for those whose transbronchial biopsy is negative or for whom a confirmatory biopsy cannot be performed.…”
mentioning
confidence: 99%